ANALISIS KARAKTERISTIK ARUS DI SELAT OMBAI BERDASARKAN DATAINSTANT TAHUN 2004-2006 - Syifa Widyastuti, Maraya
Characteristic of sea currents in the northern and southern parts of Ombai Strait has been investigated by using velocity data from International Nusantara Stratification and Transport (INSTANT) Program for the years 2004-2006. Research results show that mean current velocity in the southern part of the Ombai Strait is stronger than that in the northern part of the strait. In addition, sea current characteristic in the Ombai Strait is affected by circulation systems of South Java Current (SJC), South Java UnderCurrent (SJUC), and Indonesian Throughflow (ITF). Monsoon and interannual phenomena (El Niño Southern Oscillation/ENSO and Dipole Mode/DM) influence sea current characteristic in the Ombai Strait. The SJC in the surface layer of the strait flows eastward (westward) during the west (east) monsoon and the SJUC flows eastward at the intermediate depths (400-800m) during the monsoon transition period, whereas the ITF flows westward across the entire strait. The strongest ITF is found during the east monsoon in the subsurface (150-300 m) and it also exists during the west monsoon at the intermediate depths (400-800m). During El Niño (La Niña) event that coincided with negative IOD (positive IOD), the ITF in the Ombai Strait weakens (strengthens), whereas the eastward SJC strengthens (weakens).